2020
DOI: 10.1016/j.invent.2020.100345
|View full text |Cite
|
Sign up to set email alerts
|

Investigating mediated effects of fear of COVID-19 and COVID-19 misunderstanding in the association between problematic social media use, psychological distress, and insomnia

Abstract: Introduction Due to the serious situation of the novel coronavirus disease 2019 (COVID-19) worldwide, many countries have implemented policies to minimize the spread of COVID-19 infection. However, some of these policies prevent people from physical contact. Consequently, many individuals may rely on social media to obtain information concerning COVID-19. Unfortunately, social media use (especially problematic social media use) may give rise to psychological distress. Therefore, this study thus ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
218
5
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(245 citation statements)
references
References 32 publications
15
218
5
7
Order By: Relevance
“…Surprisingly, social media use had not changed according to most people compared to before the COVID-19 pandemic, and changes in social media use were also not significantly associated with participants' current level of emotional or social loneliness. This is not in line with other studies that reported an increase in social media use during the COVID-19 pandemic, and an association with loneliness, anxiety and depression [29][30][31]. It might be that this mainly holds for younger participants, as the age of participants in these studies was much lower.…”
Section: Positive Effectscontrasting
confidence: 95%
“…Surprisingly, social media use had not changed according to most people compared to before the COVID-19 pandemic, and changes in social media use were also not significantly associated with participants' current level of emotional or social loneliness. This is not in line with other studies that reported an increase in social media use during the COVID-19 pandemic, and an association with loneliness, anxiety and depression [29][30][31]. It might be that this mainly holds for younger participants, as the age of participants in these studies was much lower.…”
Section: Positive Effectscontrasting
confidence: 95%
“…Specifically, in the general population, fear increased preventive measures [ 23 ], but it decreased health behavior among people with mental illness [ 24 ]. Social media also influence fear, and the public’s problematic information may increase fear and distress, impeding effective coping with the disease [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the importance of assessing psychological responses toward COVID-19 and their associated factors has been highlighted in the extant literature. More specifically, adverse effects of elevated psychological distress may trigger reassurance-seeking and compulsive-checking behaviors in response to potential threats of COVID-19 infection, which, in turn, may have an impact on the daily lives of individuals who impede preventive behaviors [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the HBM and PMT, the literature proposes the importance of obtaining accurate COVID-19 information from trusted sources. Indeed, misinformation concerning COVID-19 is associated with a greater fear of the disease [ 15 , 16 ]. Hou et al [ 31 ] reported that rumors and misinformation shared on the internet may induce panic behaviors such as purchasing herbal remedies via web-based shopping and storing them.…”
Section: Introductionmentioning
confidence: 99%